Metody kauzální analýzy pro měření efektivity podpory prodeje - Králová, Maria (Masaryk University Press, 2021)
Title in English: Methods of causal analysis for measuring the sales support eﬃciency. In recent years, company costs associated with sales promotion activities have continued to rise in developed economies, and yet many studies show that such sales promotion activities are very often unproﬁtable, and in many cases even result in losses. One cause of this undesirable phenomenon may be inadequate analytical tools. The use of adequate analytical tools would make it possible to reliably measure the eﬀectiveness of sales promotion activities. The most commonly used analytical tools often lead to biases when estimating the eﬀectiveness of promotion activities. This is because these tools cannot take into account a number of factors which change over time, may aﬀect the proﬁtability indicators and are not controlled when performing an estimate with the common tools. The monograph oﬀers a new approach to estimating baseline sales (i.e. the sales ﬁgures as they would be if sales promotion activity had not taken place) using causal analysis methods. The suggested approach removes the bias of an estimator resulting from the change of factors over time, while at the same time it is simple enough to be implemented in common business practice. The monograph also presents the methods of causal analysis. Despite their potential to successfully deal with a number of marketing and management issues, these methods are rarely used, either in the Czech Republic or internationally.